BIMBINGAN KONSELING ISLAM DENGAN TEKNIK BIBLIOTERAPI DALAM MENGATASI DEKADENSI KEIMANAN MAHASISWA DI SURABAYA - Zainuri, Ahmad; Rahmawati, Pudji (Jurnal Bimbingan dan Konseling Islam, 2022)
he study aims to determine the Process Guidance and Counseling Islam with bibliotherapy Techniques in Addressing Decadence All imanan A student in Surabaya, as well as the results of Guidance And Counseling Islam with bibliotherapy Techniques in Addressing Decadence All imanan A student in Surabaya. The method used in this research is descriptive qualitative, whereas the type of case study research. In this research, writer and counselor provides guidance and counseling Islam with measures of counseling that includes the step of problem identification, diagnosis, prognosis, treatment and evaluation. Having held counseling, this study considered quite successful. This is consistent with a score of 60% which tegolong in category 60% - 65%. The success of this research can be seen from the reduced indicators of the problem, namely the loss of 6 symptoms of decadence faith than ever that there are 10 symptoms.